Sosialisasi Pembuatan Pestisida Alami untuk Pengendalian Hama Tanaman dalam Mendukung Kehidupan Berkelanjutan di Majalengka - Gusman Santika; Retno Ayu Puspita; Sarina Hanifah; Hermawan; Muhammad Raka Faizan; Nazla Sabila; Pramesti Nawang Sari (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Majalengka is an agrarian regency in West Java with a high dependence on the agricultural sector; however, its communities have not yet optimally utilized natural materials as alternatives to chemical pesticides, which pose significant risks to the environment and human health. This community service activity aimed to improve the knowledge of Majalengka residents regarding the production and application of natural pesticides derived from soursop leaves (Annona muricata L.) and red onion peel as eco-friendly plant pest control agents. The methods employed included material dissemination, pesticide-making demonstrations, and the distribution of experimental kits and guidebooks to 20 participants from the Rumah Keluarga Indonesia (RKI) women's group affiliated with JSIT Majalengka Regency. Evaluation was conducted using a 10-item questionnaire with a Cronbach's alpha reliability coefficient of 0.913. Results showed an increase in participants' knowledge from an average of 62.92% (low category) before the activity to 86.25% (high category) afterward, with a participant satisfaction rate of 88.75%. The activity concluded that experimental kit-based socialization is effective in enhancing community understanding of natural materials as affordable and eco-friendly botanical pesticides, while also encouraging participants' intention to apply them independently.